Analisis Peran Pemerintah Daerah dalam Mengatasi Masalah Sosial di Tingkat Daerah - Adis Haditsamanar; Ilham Ubaidillah; Siti Nazwa Holidaziah; Dini Safinah; Refita Cahyani; Nessya Arditia Helmi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Social issues such as poverty, unemployment, social inequality, limited access to education, and inadequate healthcare services remain major challenges in regional development in Indonesia. Local governments play a strategic role in addressing these issues through their functions as regulators, facilitators, and innovators in public policy implementation. This study aims to analyze the role of local governments in overcoming social problems at the regional level and to identify factors influencing the effectiveness of their interventions. A descriptive qualitative approach was employed using a literature review of relevant academic sources. Data were analyzed through identification, classification, and interpretation processes to obtain a comprehensive understanding of local government policies and strategies in addressing social issues. The findings indicate that the success of local governments is influenced by the quality of governance, institutional capacity, resource availability, inter-agency coordination, and community participation. Community empowerment programs, including skills training, business assistance, and local economic development initiatives, have proven effective in improving social welfare. Inclusive, data-driven, and sustainable policies also contribute to reducing regional disparities and promoting equitable development. Strong collaboration among local governments, communities, and the central government is essential for achieving more responsive, equitable, and sustainable regional development.